Management of non-muscle invasive bladder cancer: A comprehensive analysis of guidelines from the United States, Europe and Asia. (June 2016) - Tan, Wei Shen; Rodney, Simon; Lamb, Benjamin; Feneley, Mark; Kelly, John
Highlights: All guidelines have minor variation on upper tract imaging and endoscopic treatment. Surveillance recommendations in low-risk patients vary significantly. Only NICE had recommendations on photodynamic cystoscopy and urinary biomarkers. No intravesical treatment options other than Mitomycin C and BCG were recommended. Device assisted intravesical treatment are promising but further trials are needed. Abstract: Bladder cancer is the 8th most common cancer with 74, 000 new cases in the United States in 2015. Non-muscle invasive bladder cancer (NMIBC) accounts for 75% of all bladder cancer cases. Transurethral resection and intravesical treatments remain the main treatment modality. Up to 31–78% of cases recur, hence the need for intensive treatment and surveillance protocols which makes bladder cancer one of the most expensive cancers to manage. The purpose of this review is to compare contemporary guidelines from Europe, (European Association of Urology), the United States (National Comprehensive Cancer Network), the United Kingdom (National Institute for Health and Care Excellence), Japan (Japanese Urological Association) and the International Consultation on Bladder Cancer (ICUD). We compare and contrast the different guidelines and the evidence on which their recommendations are based.